Teknik dan Taktik Pembelajaran Tari Kreasi Bakul Melalui Metode Kerja Kelompok pada Siswa Kelas XI IPA 2 di SMA Negeri 11 Palembang - Andriani, Andriani; Elvandari, Efita; Hidayatullah, Fadhilah (Indonesian Research Journal on Education, 2022)
The purpose of this study was to describe the techniques and tactics of learning basket dancecreations through group work methods for students of class XI IPA 2 at SMA Negeri 11 Palembang. The focus of the research is on learning basketry dance creations using the group work method. While the sub-focus of this research is the techniques and tactics through the group work method in learning the creation of bakul dance for class XI science 2. The research problem is how are the techniques and tactics for learning the basket dance through the group work method for students of class XI science 2. The method used in this study is a qualitative method. The samples of this study were students of class XI IPA 2. The data collection techniques used in this study were observation, interviews, and documentation. the value of 86 from the value of 86-100 with the criteria of "Very good" totaling 5 students and the value of 71-85 with the criteria of "Good" with an average value of 71 totaling 26 students can be categorized as good. Learning is carried out in three stages of activity, namely, preparation, implementation, and evaluation. In learning the art of basketry dance, the teacher uses a group work method where students are divided into several groups and the teacher teaches the dance.